Assessing Salmonella quantification methods: MPN and MPN-LAMP perform equally in artificial contamination, while dPCR lacks sensitivity for naturally contaminated samples - Silva, Evelyn Cristine; Laurindo, Amanda Louise; Minatel, Vitória Meneghetti; Pereira, Juliano Gonçalves; Araújo Júnior, João Pessoa; Possebon, Fábio Sossai (Food Science and Technology, 2025)
Identifying and quantifying Salmonella in chicken carcasses is crucial for food safety and public health. Recent efforts focus on improving detection methods by combining traditional microbiology with molecular biology for better accuracy and speed. This study compared two protocols for Salmonella quantification: the conventional most probable number (MPN) and a combined approach integrating MPN with loop-mediated isothermal amplification (LAMP). The second phase evaluated MPN-LAMP and digital polymerase chain reaction for detecting and quantifying Salmonella in naturally contaminated chicken samples. The results indicated no statistically significant difference between the conventional MPN and MPN-LAMP methods in the evaluated steps. Both methods had similar performance, suggesting that MPN-LAMP can be used as a faster alternative. Upon application of this methodology to naturally contaminated chicken carcasses, 4 out of 16 samples (25%) exhibited contamination levels exceeding the detection thresholds when quantified using the MPN-LAMP method, with values ranging from 3.6 MPN/g to 15 MPN/g. However, the digital polymerase chain reaction technique could not detect or quantify samples in naturally contaminated chicken carcasses, highlighting challenges in pathogen detection in food. The results emphasize the need to compare methods in routine samples for microbiological surveillance and improve quantification techniques, ensuring food safety and implementing innovative Salmonella detection protocols.